Real-time network simulation support for scalable routing experiments. (22nd September 2009) - Li, Yue; Liu, Jason; Rangaswami, Raju
This paper describes a new software infrastructure that combines the scalability and flexibility benefits of real-time network simulation with the realism of open-source routing protocol implementations. The infrastructure seamlessly integrates the open-source XORP router implementation with a real-time large-scale network simulation engine. The design uses a novel forwarding plane offloading approach that decouples routing from forwarding and confines the more resource consuming forwarding operations inside the simulation engine to reduce I/O overhead. Experiments demonstrate superior performance of the software routing infrastructure without impairing accuracy. The infrastructure is shown to be able to support large-scale routing experiments on light-weight virtual machines.